2022
DOI: 10.3389/fonc.2022.843325
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase N2 as a Novel Diagnostic and Prognostic Biomarker for Lung Adenocarcinoma

Abstract: Carboxypeptidase N2 (CPN2) is a plasma metallo-protease that cleaves basic amino acids from the C-terminal of peptides and proteins. Emerging evidence showed that carboxypeptidases perform many diverse functions in the body and play key roles in tumorigenesis. However, the clinical significance and biological functions of CPN2 in lung adenocarcinoma remain unclear. Our study aimed to explore the potential role and functions of CPN2 in lung adenocarcinoma. The results showed that the transcription level of CPN2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
1
Order By: Relevance
“…Eleven mRNAs (ING3, SNF1LK2, SYF2, CPN2, EPB42, EMCN, HADH, DTWD1, PYGM, EPN3, SPINT2) with at least one or more other tumor-related study were found. The expression patterns of SYF2 and CPN2 in other breast cancer studies and in studies of other tumor types were both opposite to the findings of this study [ 22 , 23 , 24 , 25 ]. In addition, EPN3 was upregulated in other breast cancer-related studies, similar to this study, but was downregulated in gastric cancer and upregulated in glioblastoma, with the opposite results [ 26 , 27 , 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Eleven mRNAs (ING3, SNF1LK2, SYF2, CPN2, EPB42, EMCN, HADH, DTWD1, PYGM, EPN3, SPINT2) with at least one or more other tumor-related study were found. The expression patterns of SYF2 and CPN2 in other breast cancer studies and in studies of other tumor types were both opposite to the findings of this study [ 22 , 23 , 24 , 25 ]. In addition, EPN3 was upregulated in other breast cancer-related studies, similar to this study, but was downregulated in gastric cancer and upregulated in glioblastoma, with the opposite results [ 26 , 27 , 28 ].…”
Section: Discussioncontrasting
confidence: 99%